2017
DOI: 10.1016/j.jagp.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Loss and Α-Synuclein Pathology in the Superior Colliculus and Its Relationship to Visual Hallucinations in Dementia with Lewy Bodies

Abstract: These findings suggest that regions involved in directing attention toward visual targets are subject to neurodegenerative changes in DLB. Considering several hypotheses of visual hallucinations implicating dysfunctional attention toward external stimuli, these findings may provide evidence of pathologic changes that contribute to the manifestation of visual hallucinations in DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…A subset of DLB cases (9/14) used for histological analysis had been subject to neuropsychological evaluation intra vitam. As detailed previously, these individuals had been assessed using the hallucinations subscale of the Neuropsychiatric Inventory (NPI) within 2 years prior to death . Comparison of the NPI hallucination score with neuropathological markers and GFAP demonstrated a significant positive correlation only between tau burden and NPI hallucination subscale score ( r s = 0.701, P = .035).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of DLB cases (9/14) used for histological analysis had been subject to neuropsychological evaluation intra vitam. As detailed previously, these individuals had been assessed using the hallucinations subscale of the Neuropsychiatric Inventory (NPI) within 2 years prior to death . Comparison of the NPI hallucination score with neuropathological markers and GFAP demonstrated a significant positive correlation only between tau burden and NPI hallucination subscale score ( r s = 0.701, P = .035).…”
Section: Resultsmentioning
confidence: 99%
“…To quantify glial subpopulations and neuropathological lesions in the pulvinar in a separate cohort of cases and α‐synuclein pathology in the amygdala of the cases used for the transcriptomic study, images were taken on a Zeiss AxioVision Z.1 microscope using a DsFi1 camera (Nikon, Japan). As detailed previously, Stereologer software was used to delineate a region of interest with a 2.5 × objective, prior to the placement of disector frames in a uniform, random arrangement. This method prevented the introduction of bias by giving every area of the region of interest an equal probability of being sampled for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The Braak hypothesis proposes that the main PD pathological process starts at the olfactory bulb and/or peripheral gastrointestinal nerve terminals, with secondary spread to the brainstem through the autonomic system . This prionlike phenomenon also targets the SC . The SC is a rich, complex, and widely connected entity, including a mutual inhibitory connection between each SC (Fig A) .…”
Section: Discussionmentioning
confidence: 99%
“…6 This prionlike phenomenon also targets the SC. 20 The SC is a rich, complex, and widely connected entity, including a mutual inhibitory connection between each SC ( Fig 4A). 21 Previous studies have found not only pathological α-synuclein accumulation in the human SC but also a more severe pathology in the SC layers connected to some midbrain structures, especially the dorsal raphe, the locus coeruleus, and the pedunculopontine nucleus (see Fig 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a certain degree of neuronal integrity may be required for psychosis in Alzheimer's disease. A recent study of patients who had dementia with Lewy bodies found that the severity of hallucinations was positively correlated with neuronal density in the stratum griseum superficiale of the superior colliculus . This finding lends credulity to the notion that structure‐specific neurodegeneration can effect cessation of psychotic phenomena .…”
Section: Discussionmentioning
confidence: 80%